The tendon graft wrap repair in flexor zone 5 injuries - Echeverria, Alfonso; Clifton, Jorge; Reynoso, Rafael (International Journal of Research in Medical Sciences, 2022)
Tendon lacerations are commonly presented in hand injuries. Within flexor tendons, zone 5 has not been a spotlight topic in the literature although it encompasses important tendons involved in wrist stability. The aim of the study was to highlight the importance of tendon repair in flexor zone 5 introducing a novel technique. In this article we described our new surgical technique use at the plastic and reconstructive surgery unit of the General Hospital of Mexico with 4 different flexor tendon zone 5 injuries. All cases included a HBRT laceration in this zone. We also describe its variances for reconstruction based on our proposed tendon territory classification. Our tendon injury classification is based on anatomical features and may be useful for repair planning. Our technique is based on a ‘like with like’ tendon supply to achieve a strong biomechanical reinforcement. TGW technique was a reliable reinforcement on primary tendon repair after using a conventional tenorrhaphy. Tendon reconstruction still has a field of research and improvements. Our work stands out some specific tendon requirements and relevant territories. We propose a simple management with a novel technique.